Discharge Outcomes of Severely Sick Patients Hospitalized with Multidrug-Resistant Tuberculosis, Comorbidities, and Serious Adverse Events in Kyrgyz Republic, 2020–2022 - Gulzat Alumkulova; Anna Hazoyan; Elena Zhdanova; Yuliia Kuznetsova; Jaya Prasad Tripathy; Aelita Sargsyan; Olga Goncharova; Meder Kadyrov; Kylychbek Istamov; Nimer Ortuño-Gutiérrez (Tropical Medicine and Infectious Disease, 2023)
Patients with multidrug-resistant tuberculosis (MDR-TB) who have comorbidities, complications, and experience serious adverse events (SAEs) are at substantial risk of having unfavorable hospital outcomes. We assessed characteristics and discharge outcomes of 138 MDR-TB patients hospitalized in the National Referral Center of Bishkek, Kyrgyz Republic, from January 2020 to August 2022. The main clinical characteristics included pulmonary complications (23%), malnutrition (33%), severe anemia (17%), diabetes mellitus (13%), viral hepatitis B and C (5%), and HIV infection (3%). Of those patients, 95% were successfully managed and discharged from hospital. Seven patients had unfavorable discharge outcomes (three patients died and four had a worsened clinical condition). Comorbidities (diabetes, and/or HIV), severe anemia, pulmonary complications, cardiovascular disorders, alcohol abuse, and SAEs were associated with unfavorable discharge outcomes. Sixty-five percent of the patients had SAEs, with electrolyte imbalance (25%), gastrointestinal disease (18%), hepatotoxicity (16%), and anemia (14%) being the most frequent. Successful resolution occurred in 91% of patients with SAEs. In summary, our study documented that sick patients who were hospitalized with MDR-TB were well managed and had good hospital discharge outcomes, despite the fact that they had comorbidities, complications, and SAEs. This information should assist in the referral and management of such patients in the future.